In situ control of oxygen partial pressure in a buffered UO2 fuel: A manufacturing process. Issue 4 (April 2020) - Khair, M.; Riglet-Martial, Ch.; Matheron, P.; Lechelle, J.; Palancher, H.; Iltis, X.; Tarisien, N.; Heintz, J.-M.
Abstract: An innovative laboratory process making use of the specific properties of solid redox buffers was developed for producing O2 self-regulated UO2 fuel samples. The method was optimized using Molybdenum and Niobium oxide buffers. The starting materials were first mixed with the UO2 powder, then pressed into pellets and finally sintered in a quasi-closed vessel at 1670 °C under strictly controlled oxygen potential using appropriate solid redox buffers. Speciation of Mo and Nb was characterized using Scanning Electron Microscopy (SEM) combined with Energy Dispersive X-ray spectroscopy (EDX) as well as X-ray Diffraction (XRD). Using this optimized procedure, both oxido-reducing forms of the O2 buffer incorporated into the UO2 specimens were preserved during sintering, allowing an in situ control of the O2 partial pressure inside the material. The processing methodology, the laboratory experimental set-up, the sintering procedure and the characteristics of the final oxygen buffered UO2 fuel are described. This work opens the path to representative laboratory studies related to the redox dependent behavior of irradiated fuels in reactor.